Skip Grand Visions for Software Development: Authors’ Response. - Jacobson, Ivar; Seidewitz, Ed (Communications of the ACM, 2015)
A reply from the authors is presented in response to a letter to the editor in the current issue from Dean Wampler concerning the article "A New Software Engineering" by Ivar Jacobson and Ed Seidewitz, which appeared in the December 2014 issue.